BUILDING STUDENTS' ENVIRONMENTAL CARING CHARACTER THROUGH SOCIAL SCIENCE EDUCATION - Emil El Faisal; Umi Chotimah; Sulkipani Sulkipani (Sriwijaya University Learning and Education International Conference, 2018)
This literature review aims to analyze the concepts and ideas of building the character of the students' environment through social science. The background of this study is the occurrence of various damage and deterioration of environmental quality that negatively impact the whole human life. A preventive effort is needed to prevent environmental damage through planned and systematic efforts to build environmental awareness for the community. These efforts can be done through education. Education as an effort to change the paradigm of thinking in the direction of self-discretion. That is, through education awareness of the environment can be realized. In educational units, there are subjects of social science that examine people in a social context. In principle, the environment within the social science context not only addresses the human social environment, but also includes the physical environment, the biotic and abiotic environments that support human life. Through social science is expected learners are expected to build environmental awareness, so that sustainability and environmental balance can be realized.